Performance of varieties of Gboma (Solanum macrocarpon) under disease pressure with organic amendment in Southern Benin - Sikirou, R.; Hoteigni, J.; Godonou, I.; James, B.; Grehounou, G.; Assogba-Komlan, F. (2011)
‘Gboma’, the African eggplant, is one of the traditional vegetables in Benin that has not been studied in terms of varietal differences and reaction to diseases. Colletotrichum stem rot of Solanum macrocarpon ‘Gboma’ is a widespread disease in S. macrocarpon cultivated areas of South Benin. This study is focused on the disease diversity on S. macrocarpon and determines the behaviour of the varieties of S. macrocarpon to diseases using different doses of organic fertiliser. The appearance of disease symptoms was investigated in two locations (Cotonou and Sèmè) on six S. macrocarpon varieties fertilised with 20 t ha-1 and 40 t ha-1 of chicken manure in a completely randomised block design with 4 replications. The stem rot of S. macrocarpon caused by the fungus Colletotrichum capsici was the only recorded disease. The incidence of the disease was measured as area under the incidence progress curve. The disease incidence was significantly higher in Somalie Gboma variety and significantly lower in the Abidjan Gboma variety at both locations. Regarding the effect of amended manure, the disease incidence was low in plots amended with 40 t ha-1 and high in those amended with 20 t ha-1, with significant differences (p = 0.0237) obtained in the Cotonou location. This is in Benin the first record of C. capsici as pathogen of S. macrocarpon with positive Koch postulate reaction and of the Abidjan Gboma as resistant variety of S. macrocarpon to C. capsici. For this disease reduction and yield increase, organic amendment of 40 t ha-1 chicken manure is recommended.